2021
DOI: 10.1088/2053-1591/ac343e
|View full text |Cite
|
Sign up to set email alerts
|

Near-optimal composition of CZTS thin film via exploration of copper and thiourea molar concentration in spray pyrolysis technique

Abstract: Attaining the optimal composition of Cu2ZnSnS4 (CZTS) thin film is a pre-requisite for photovoltaic application. Herein, the near-optimal composition of spray pyrolyzed CZTS thin film has been obtained by varying copper and thiourea molar concentrations in the precursor solution. Different characterization techniques such as x-ray diffraction (XRD), UV–vis spectroscopy, Scanning electron microscopy (SEM) and Energy-dispersive x-ray spectroscopy (EDS) have been employed to determine the changes in absorber laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
1
3
1
Order By: Relevance
“…The band gap values of the films S-0 to S-5 are found to be 1.62, 1.58, 1.55, 1.4, 1.38, and 1.6 eV, respectively. Band gap of the as-deposited thin films grown at 300 °C substrate temperature agrees well with the values reported by other researchers [48]. Figure 7 exhibits the variation of band gap for all samples, which shows that the value of the direct optical band gap gradually decreases with the increase in copper content, and sulfurization, which is concurrent to the reported values [20].…”
Section: Optical Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…The band gap values of the films S-0 to S-5 are found to be 1.62, 1.58, 1.55, 1.4, 1.38, and 1.6 eV, respectively. Band gap of the as-deposited thin films grown at 300 °C substrate temperature agrees well with the values reported by other researchers [48]. Figure 7 exhibits the variation of band gap for all samples, which shows that the value of the direct optical band gap gradually decreases with the increase in copper content, and sulfurization, which is concurrent to the reported values [20].…”
Section: Optical Propertiessupporting
confidence: 89%
“…A similar effect is observed in our samples. It was reported that a higher copper concentration leads to increased band gap [48], whereas, in this study it was found that addition of copper reduces the band gap of the samples, in comparison to the as-deposited sample. According to our study, the ideal copper content may be between 25%-26% for a low bandgap within 1.4 to 1.5 eV, for optimal use of the CZTS thin film as an absorber layer in a thin film solar cell structure.…”
Section: Optical Propertiescontrasting
confidence: 55%
“…6 using a 325 nm wavelength. The CuS is known to segregate on the surface in the form of easily visible large grains 68 . This confirms the conclusions of GIXRD analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Different chemical and physical approaches have been employed to synthesize CZTS thin films, such as electrodeposition, sol–gel, spray pyrolysis, evaporation, pulsed laser deposition, and magnetron sputtering . Among these techniques, magnetron sputtering allows the production of highly crystalline CZTS films on large-area substrates.…”
Section: Introductionmentioning
confidence: 99%